History of Azerbaijan Turkish Philosophy Sources, Formation and Development - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2021)
The article shows that the process of writing the history of AzerbaijanTurkish philosophy and its formation as a science has gone through a complicated process. It has long been assumed that the history of national philosophy in Azerbaijan began with the work of academician Heydar Huseynov, From the history of social and philosophical thought in Azerbaijan in the nineteenth century, published in 1949. However, according to the author, the historiography of national philosophy is not as purely scientific and philosophical as the academic style of Huseynov, but is connected with the fundamental work Literature of Azerbaijani Turks written by AzerbaijaniTurkish thinker Firudin bey Kocharli in the 1900s. Kocharli covered not only literary issues, but also socio-philosophical problems in that work. In other words, as Kocharli himself noted, in this work, in addition to the "poet-gabil", he also studied and analyzed the cultural and philosophical heritage of the thinkers he called "literary-fazil". At the same time, A.A.Bakikhanov, A.Sur, Y.V.Chamenzaminli, M.Tarbiyet, S.Mumtaz, M.A.Rasulzadeh and others, who in one way or another took part in the philosophical and public opinion of the Azerbaijani people in their works before H.Huseynov, in the article. The "philosophical historian" is also touched upon, albeit briefly. After that, the author focused on H.Huseynov’s philosophical historiography, tried to show the place and role of his work in the philosophical historiography of the Azerbaijani people. According to the author, Huseynov’s philosophical historiography aimed at studying the philosophical and public opinion of the Azerbaijani people in the academic style was continued by M.Gasimov, Z.Guluzade, F.G.Kocharli, M. Agamirov, Z. Mammadov and others. In this regard, the article focuses on the works of Z.Goyushov, Z.Guluzade, Z.Mammadov and others on the social and philosophical thought of the Azerbaijani people in different periods or in general. According to the author, "Essays on the history of Azerbaijani philosophy" published by a team of authors during the Soviet Union can be considered the first systematic, large-scale book on the history of Azerbaijani Turkish philosophy. The article shows that after the restoration of Azerbaijan’s independence, the publication of the first two volumes of the multi-volume History of Azerbaijani Philosophy was an important event in Azerbaijani science, especially in the history of national philosophy. The article also notes that against the background of the fact that the volumes on the 19th and 20th centuries after the first two volumes reflecting the history of Azerbaijani Turkish philosophy, including the 18th century, have not yet been published, the publication of Faig Alakbarli’s three-volume History of Azerbaijani Turkish Philosophical and Public Thought was important in filling this gap.